Field investigation on Hypomagnesaemic and Hypocuprosis in Cattle in Baghdad Provience - .S., Dr. Al-Juburii , K.O (The Iraqi Journal of Veterinary Medicine, 1999)
This field investigation has been coducted on 5l animals from different areas in baghdad provience . Their ages ranged from 10days to 7years. They were devided into two groups . Group 1 consisted of 26 animals showed signs of hypomagnesaemia and hypocuporosis · The result indicated asignificance decrease in magnesium level (p <0.01 ) which asgnificance decrese in magnesium and cuppor levels (p <0.01) which were less than 1.6 mg/100 ml respectivly especially in calves ranged 2-4 months of age. The result of group 2 which consisted of 25 animals (control) indicated that the percentage of magnesium and cupper were within normal range.